2014
DOI: 10.1002/bit.25184
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Staphylococcus aureus α‐hemolysin as a protein drug that is secreted by anticancer bacteria and rapidly kills cancer cells

Abstract: Targeted bacterial delivery of anticancer proteins has the ability to overcome therapeutic resistance in tumors that limits the efficacy of chemotherapeutics. The ability of bacteria to specifically target tumors allows for delivery of aggressive proteins that directly kill cancer cells and cannot be administered systemically. However, few proteins have been tested for this purpose. To identify effective molecules, we systematically sorted proteins that have been shown to cause mammalian cell death. The genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 49 publications
5
36
0
1
Order By: Relevance
“…The results of our study are consistent with the previous study by Swofford et al (2014) that demonstrated VNP20009’s ability to express an active form of the Pseudomonas ToxA capable of killing cancer cells (Figs. 1 and 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of our study are consistent with the previous study by Swofford et al (2014) that demonstrated VNP20009’s ability to express an active form of the Pseudomonas ToxA capable of killing cancer cells (Figs. 1 and 2).…”
Section: Discussionsupporting
confidence: 93%
“…In vitro, this attenuated Salmonella strain is able to locally induce apoptosis of tumor cells (Ganai et al, 2011) but its culture supernatant exhibits little ability to kill cancer cells (Swofford et al, 2014). Augmenting the ability to kill cancer cells by a secreted protein targeted to the tumor cells themselves might compensate for the lack of antitumor activity in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirmed that alpha hemolysin toxin is used as anticancer. These results are agreement with those published by Bantel et al (2001); Swofford et al (2014). In this connection, Vandenesch et al (2012) has reported that α-hemolysin is the most characterized virulence factor of S. aureus.…”
Section: Application Of Recombinant α-Hemolysin Protein In Different supporting
confidence: 93%
“…(4-C). α-toxin protein was expressed at 34 KDa and this result is agreement with those published by Bantel et al (2001) and Swofford et al (2014).…”
Section: Cloning Of Alpha Hemolysin Toxin Gene Into Ph6htnhishalotagtsupporting
confidence: 90%